Effects of Different Temperature-Time Combinations on Protein Absorption Characteristics of Sous-Vide Cooked Beef Tendon - LI Tianyi, SUN Jian (Shipin Kexue)
In this study, marinated beef tendon was subjected to sous-vide cooking under different combinations of temperature and time. Traditional high-temperature stewing was used as a control. The cooked meat was digested in vitro and the digest was added to an in vitro absorption model based on Caco-2 cells to simulate the absorption process. The effects of different temperature-time combinations on the protein absorption of sous-vide cooked beef tendon were determined by measuring the protein absorption products. The results showed that sous-vide processing increased the absorption of free amino acids and peptides especially those with small molecular mass of 300-500 Da. Sous-vide cooking at 60 ℃ favored the absorption of myosin and actin, while sous-vide cooking at 80 ℃ favored the absorption of collagen. Compared with the other treatment groups, sous-vide cooking at 60 ℃ for 8 h resulted in the occurrence of significantly more essential amino acids and antioxidant amino acids as well as more small-molecular-mass peptides and specific bioactive peptides in the absorbed products, showing higher nutritional levels.